Carnosine supplementation and retinal oxidative parameters in a high-calorie diet rat model - de Almeida Torres, Rogil Jose [UNESP]; Moreto, Fernando [UNESP]; Luchini, Andrea; de Almeida Torres, Rogerio Joao; Longo, Sofia Pimentel; Pinho, Ricardo Aurino; Nagashima, Seigo; de Noronha, Lucia; Ferron, Artur Junio Togneri [UNESP]; de Almeida Silva, Carol Cristina Vagula [UNESP]; Corrêa, Camila Renata [UNESP]; Aldini, Giancarlo; et al. (Springer Nature, 2023)
Background: To assess oxidative effects induced by a high-calorie diet on the retina of Wistar rats and test the antioxidative effects of carnosine supplementation. Methods: Wistar rats were randomly divided into the following groups: standard diet (SD), high-calorie diet (HcD), standard diet + carnosine (SD + Car), and high-calorie diet + carnosine (HcD + Car). The body weight, adiposity index, plasma glucose, total lipids, high-density lipoprotein (HDL), low-density lipoprotein (LDL), uric acid, creatinine, and triglycerides of the animals were evaluated. The retinas were analyzed for markers of oxidative stress. Hydrogen peroxide production was assessed by 2',7'-dichlorodihydrofluorescein diacetate (DCF) oxidation. The total glutathione (tGSH), total antioxidant capacity (TAC), protein carbonyl, and sulfhydryl groups of the antioxidant system were analyzed. Results: TAC levels increased in the retinas of the SD + Car group compared to the SD group (p < 0.05) and in the HcD + Car group compared to the HcD group (p < 0.05). The levels of GSH and the GSSH:GSSG ratio were increased in the HcD + Car group compared to the SD + Car group (p < 0.05). An increase in the retinal carbonyl content was observed in the HcD group compared to the SD group (p < 0.05) and in the HcD + Car group compared to the SD + Car group (p < 0.05). A high-calorie diet (HcD) was also associated with a decrease in retinal sulfhydryl-type levels compared to the SD group (p < 0.05). Conclusion: The results suggest that feeding a high-calorie diet to rats can promote an increase in carbonyl content and a reduction in sulfhydryl groups in their retinas. The administration of carnosine was not effective in attenuating these oxidative markers. Trial registration: Animal Ethics Committee of Botucatu Medical School - Certificate number 1292/2019.
Keywords: Antioxidant; Carnosine; High-calorie diet; Retina